Mechanic: resurrection [videorecording (Blu-Ray + DVD)] - Shelby, Philip; Mosher, Tony; Statham, Jason, 1967-; Alba, Jessica, 1981-; Jones, Tommy Lee, 1946-; Yeoh, Michelle, 1962-; Hazeldine, Sam, 1972-; Isham, Mark (Lionsgate, 2016)
Retired assassin Arthur Bishop is living undercover in Brazil when an old acquaintance kidnaps the woman Arthur loves and orders him to perform three kills.